Pengaruh Pemberian Konsentrasi Mol Pelepah Kelapa Sawit terhadap Pertumbuhan Tanaman Padi (Oryza Sativa L.) Varietas Karya Pelalawan - Wulandari, Sri; Azmi, Yudia; Febrianti, Febrianti (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2024)
The Karya Pelalawan rice variety is one of the rice varieties originating from Pelalawan. One of the problems in cultivating this plant is the use of inorganic fertilizers in the long term which can cause damage, so an alternative organic fertilizer is needed, namely Local Microorganism (MOL). MOL can be made from organic materials, one of which is palm fronds. This research aims to determine the effect of giving palm frond MOL concentrations and to obtain the best concentration of palm frond MOL on the growth of rice plants (Oryza sativa L.) of the Karya Pelalawan variety. This research used a Randomized Group Design consisting of 5 treatments and 4 replications, namely: P0 (control), P1 (100 ml), P2 (200 ml), P3 (300 ml), P4 (400 ml). Parameters observed included soil analysis, plant height (cm) and number of vegetative tillers. Providing a concentration of MOL oil palm fronds had a good effect on the growth of the Karya Pelalawan variety of rice plants and the best treatment was obtained in the P4 treatment with a dose of 400 ml which produced a plant height of 123.48 cm, the number of vegetative tillers was 19.25.